2023
DOI: 10.1007/s12403-023-00566-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Between Follicular Fluid Multiple Element Concentrations and Hormonal Profiles of Women with Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder among reproductive-aged women. Follicular uid quality affects early embryonic development and multiple stages of pregnancy. This study measured 12 elements in follicular uid and 5 blood hormones, aiming to identify the associations between multielement concentrations, as well as blood hormone levels, and PCOS to investigate the interference of multielement coexposure on PCOS and examine the potential roles of hormones. Eight elements (As, C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…This process involves the growth and maturation of ovarian follicles. Previous studies have reported the concentration of zinc iron was low in the serum of patients with polycystic ovarian syndrome (PCOS), which is accompanied by abnormal antral follicle development, low oocyte quality and infertility [ 26 ]. However, the impact of changes in zinc ions concentration on ovarian development is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This process involves the growth and maturation of ovarian follicles. Previous studies have reported the concentration of zinc iron was low in the serum of patients with polycystic ovarian syndrome (PCOS), which is accompanied by abnormal antral follicle development, low oocyte quality and infertility [ 26 ]. However, the impact of changes in zinc ions concentration on ovarian development is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%